Synthesis and Characterization of ZnO Nanoparticles via Thermal Decomposition for Zn(II) Schiff Base Complex - Hadeer Mohammed Subhi; Ali Taleb Bader; Hazim Yahya Al-Gubury (Universitas Gadjah Mada, 2022)
Zinc(II) oxide (ZnO) nanoparticles were easily produced in this research by thermal decomposition of the Zn(II) Schiff base complex. The ligand was synthesized via condensation of benzylamine with 2-hydroxybenzaldehyde. The Zn(II) Schiff base complex was prepared by the reaction between zinc salt and Schiff base with the molar ratio of 1:1 (metal:ligand). The binary complex powder was calcined at 700 °C to produce ZnO nanoparticles. Various methods were used to characterize the Schiff base, complexes, and nanoparticles, including 1H and 13C-NMR, FTIR, TGA, DTA thermal analysis, XRD, TEM, SEM, EDX, BET, UV-Vis Diffuse Reflectance, atomic absorption, melting point, and UV-Vis spectrophotometer. ZnO nanoparticles had an average crystallite size of 48.2 nm.